2004
DOI: 10.1128/jb.186.24.8337-8346.2004
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilisOperon Encoding a Membrane Receptor for Bacteriophage SPP1

Abstract: The results reported here have identified yueB as the essential gene involved in irreversible binding of bacteriophage SPP1 to Bacillus subtilis. First, a deletion in an SPP1-resistant (pha-2) strain, covering most of the yueB gene, could be complemented by a xylose-inducible copy of yueB inserted at amyE. Second, disruption of yueB by insertion of a pMutin4 derivative resulted in a phage resistance phenotype regardless of the presence or absence of IPTG (isopropyl-␤-D-thiogalactopyranoside). YueB homologues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 35 publications
(27 reference statements)
6
99
1
Order By: Relevance
“…Recent sequence analysis revealed that yukA-yukB represents a single ORF (31). EssC, Rv3870, Rv3871, and YukA sequences encompass one or more FSDs (17).…”
Section: A Cluster Of S Aureus Genes Encoding Esat-6-like Proteins mentioning
confidence: 99%
“…Recent sequence analysis revealed that yukA-yukB represents a single ORF (31). EssC, Rv3870, Rv3871, and YukA sequences encompass one or more FSDs (17).…”
Section: A Cluster Of S Aureus Genes Encoding Esat-6-like Proteins mentioning
confidence: 99%
“…This step involves the recognition of, and binding to, one or more cell envelope constituents, which leads to the ejection of the phage DNA from the capsid (17). The implementation of efficient phage therapies to target pathogenic bacteria requires detailed knowledge of the bacterial receptors recognized by the phages (18).…”
mentioning
confidence: 99%
“…The observed SPP1 plaque phenotype could thus be due to a polar effect of the knockout on expression of downstream genes. Such an effect was previously reported for disruption of cistrons of the yuk operon, which encodes, in order, yukE, yukD, yukC, yukB, and yueB (32). To test this possibility, titrations of the mutant strains were carried out in the presence of 1 mM IPTG.…”
Section: Resultsmentioning
confidence: 91%
“…Phage infection was significantly affected in only seven singlegene knockout mutants. Five of these genes are part of the yuk operon, shown to be involved in SPP1 entry into the host cell cytoplasm (32). The other two genes are involved in protein synthesis and in proline catabolism.…”
mentioning
confidence: 99%